2010
DOI: 10.3945/jn.109.105163
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Vaccenic Acid Has Antiatherogenic Effects in LDLr−/− Mice

Abstract: Epidemiological evidence has associated dietary trans fatty acids (TFA) with heart disease. TFA are primarily from hydrogenated fats rich in elaidic acid, but dairy products also contain naturally occurring TFA such as vaccenic acid. Our purpose in this study was to compare the effects of consuming a commercially hydrogenated vegetable shortening rich in elaidic TFA (18:1t9) or a butter rich in vaccenic TFA (18:1t11) in the absence and presence of dietary cholesterol on atherosclerosis. LDL receptor deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 35 publications
2
65
0
2
Order By: Relevance
“…Overall, there appears to be little if any increased risk of CVD from consumption of ruminant TFA, at least at current intakes. This conclusion appears to be supported by a recent study in mice, which confirmed that consuming a trans-9, C18:1-rich diet stimulates atherosclerosis, whereas consumption of a trans-11, C18:1-rich butter provides protection (Bassett et al, 2010). Confirmation in human studies is needed.…”
Section: Milk and Dairy Products As Sources Of Trans-fatty Acids (Tfa)mentioning
confidence: 77%
“…Overall, there appears to be little if any increased risk of CVD from consumption of ruminant TFA, at least at current intakes. This conclusion appears to be supported by a recent study in mice, which confirmed that consuming a trans-9, C18:1-rich diet stimulates atherosclerosis, whereas consumption of a trans-11, C18:1-rich butter provides protection (Bassett et al, 2010). Confirmation in human studies is needed.…”
Section: Milk and Dairy Products As Sources Of Trans-fatty Acids (Tfa)mentioning
confidence: 77%
“…[28] However, clinical trials suggest the opposite and indicate cis-VA as a protective factor toward cardiovascular diseases [29] (Table 2). Similarly, animal studies with spontaneously hypertensive rats [34] and LDLr( −/− ) mice [35] showed the beneficial effects of cis-VA in lowering blood pressure and lowering blood cholesterol levels.…”
Section: Palmitoleic Acid Elongation Product In Metabolic Diseasementioning
confidence: 87%
“…Animal studies [30] Lean (2:1 mix of +/cp and +/+) and obese (cp/cp) JCR:LA-cp rats, fed 3-week a control diet (0% VA) or a VA diet (1.5% w/w) VA was ↑ in plasma phospholipids versus control-fed rats Lean VA-fed rats: ↓ proportions of CD45RC+ helper cells, and T-helper cells ↓ IL-2, IL-10, and TNF-α in spleen Obese VA-fed rats: normalized IL-2 and TNF-α in MLN to those seen in lean rats [35] LDLr −/− mice fed 14-week with atherogenic diet (2% cholesterol) (CH) or 15% vaccenic butter (1.5% w/w VA) (VB) CH + VB: ↓ serum cholesterol and triglyceride levels, ↓ atherosclerosis [34] Spontaneously hypertensive rats fed 7-week with AMF (rich in VA and CLA), or AMF + sterculic oil (SO; which inhibits the conversion of VA into CLA)…”
Section: Reference Experimental or Clinical Model Major Findingsmentioning
confidence: 93%
“…This finding agrees with previous data showing that DHA lowers oxLDL uptake (62). Conversely, it is interesting to note that EA is the most abundant trans-FA found in atheromatous plaque (63,64), and we found that EA bound CD36 on SPR and aggressively increased Dii-oxLDL.…”
Section: Fatty Acid Cd36 Binding Increased Oxldl Uptakementioning
confidence: 88%